Effect of Spiritual Emotional Freedom Technique (SEFT) to Anxiety Patient Chronic Obstructive Pulmonary Disease (COPD) - Alwan Revai; Muhammad Amin; Makhfudli Makhfudli; Yuana Dwi Agustin (Universitas Bondowoso, 2020)
Introduction: COPD can affect social and psychological aspects as well as physical health. Anxiety, loss of control in self-reliance, changes in self-concept and respiratory barriers result in serious psychological changes, including fear of death and depression. There is a significant relationship between depression and anxiety with sleep quality of chronic disease patients, the higher the degree of depression the worse the quality of sleep. Spiritual Emotional Freedom Technique (SEFT) is a therapy that uses spiritual elements to reduce psychological and physical problems caused by emotional or psychosomatic. Method: This study use Quasy Experiment